The near-optimal adjustment of carbon and nitrogen allocations into different organs in early-season rice cultivars with drastically different yield components under nitrogen application - Ning, Wen; Su, Lin; Shi, Dandan; Ji, Meina; Ouyang, Xiang; Song, Qingfeng; Shao, Caihong; Zhu, Xin-Guang; Chang, Shuoqi (Frontiers in Plant Science, 2025)
IntroductionOptimized photosynthesis and transport of photosynthate from the upper three leaves in a rice plant is critical for yield formation in rice.MethodsIn this study, we selected two high-yielding early-season rice cultivars, i.e. a large-panicle inbred rice Zhongzao39 (ZZ39) and a plural-panicle hybrid rice Lingliangyou268 (LLY268) with high effective panicle number, to study the translocation of photosynthate from the flag and the basipetal 2nd leaves to the other organs under different nitrogen application scenarios. 13CO2 labeling was study the proportion of newly assimilated carbon partitioned into different organs.ResultsResults demonstrate that the ratio that 13C assimilated in the flag leaves and the basipetal 2nd leaves, and the distribution ratio 13C in the organs of ZZ39 and LLY268 cultivars were not affected by nitrogen application. However, at the booting stage, the translocation rate of photosynthate was slower under N150 compared with CK in both flag and the basipetal 2nd leaves labeled with 13C. At the grain filling stage, an average of 51% of photosynthetic products labeled with 13C was translocated to the panicle in both cultivars under CK treatment; in contrast, only 43% of leaf photosynthate was translocated to panicles in the N150 treatment. At maturity, the photosynthate labeled with 13C distribution ratio in the panicle was greater in the basipetal 2nd leaves than in the flag leaves for ZZ39, whereas the opposite was observed in LLY268. These different photosynthate allocation patterns and their responses to nitrogen application were linked with their corresponding tiller number and number of grains per panicle.DiscussionThis study shows that early-season rice has the ability to flexibly adapt their carbon and nitrogen allocation patterns to gain optimized yield components for higher yield under different nitrogen status. Early season rice can be used as a model system to study the growth strategy selection of plants to changing environment conditions.